Adolescent childbirth, miscarriage, and abortion: associations with changes in alcohol, marijuana, and cigarette use. (19th August 2019) - Tung, Irene; Beardslee, Jordan; Pardini, Dustin; Chung, Tammy; Keenan, Kate; Hipwell, Alison E.
Abstract : Background: Adolescent girls who become pregnant demonstrate greater risk for substance use than same‐aged peers. However, it remains unclear how risk relates to normative changes in adolescence. Few studies have examined adolescent substance use changes before, during, and after pregnancy and considered how pregnancy outcomes (childbirth, miscarriage, abortion) differentially influence substance use changes. The present study examined associations between different adolescent pregnancy outcomes and within‐person changes in substance use from prepregnancy to postpregnancy. Methods: Participants included 2, 450 girls (52% Black) oversampled from low‐income urban neighborhoods in Pittsburgh, PA. Participants self‐reported pregnancy outcomes and substance use frequency (alcohol, cigarette, marijuana) annually from ages 11–20. Fixed effects regressions focused on first births, first miscarriages, and first abortions occurring from ages 12–19 to test the associations between pregnancy outcomes and within‐individual changes in substance use from prepregnancy to postpregnancy. By design, models controlled for all potential time‐stable confounds,  and models included age and subsequent pregnancies as time‐varying covariates. Results: Consistent with prior studies, girls who became pregnant (20%) reported greater early risk for substance use problems than never‐pregnant adolescents, including earlier age of onset and more regular marijuana and cigarette use. Childbirth predicted a 26%–51% within‐individual reduction in alcohol, marijuana, and cigarette use that remained significantly lower than prepregnancy levels after childbirth. Alcohol and marijuana use decreased (32%–47%) after miscarriage. Abortion was not associated with long‐term changes in substance use; however, marijuana and cigarette use gradually increased (44%–46%) in the years leading up to the year of and after abortion, respectively, before returning to prepregnancy levels. Conclusions: Findings highlight important differences in adolescent substance use patterns based on pregnancy outcome. For pregnant adolescents with heightened pre‐existing risk for substance use, pregnancy may be a window of opportunity for substance use screening and behavioral intervention.